Tenosynovial Giant Cell Tumor Involving Quadriceps Muscle – A Case Report of Two Cases - Kishore Ragavendra Rajesh; J K Giriraj Harshavardhan; Sundar Suriyakumar; Mohammed Tavfiq; U Thiyagarajan; Subalakshmi Balasubramanian (Journal of Orthopaedic Case Reports)
Introduction: Tenosynovial giant cell tumors (TS-GCTs) are benign soft-tissue tumors that arise from the synovium of joints, bursae, and tendon sheath. They are classified into two major forms – localized and diffuse types with varied clinical presentation and treatment protocol. Case Report: A 38-year-old gentleman presented with complaints of left thigh swelling and pain since 18 months. He underwent aspiration and a surgical procedure elsewhere without much improvement. Diagnosis was confirmed on magnetic resonance imaging (MRI). Surgical resection was done and specimen was correlated histopathologically. Another 15-year-old boy presented with complaints of right knee pain and swelling since 5 months. MRI was done which showed knee effusion with synovial thickening for which aspiration was done and started on antibiotics but symptoms persisted. Hence, surgical resection and biopsy was done which was confirmed to be TS-GCT. Both patients regained full knee movements postoperatively and were uneventful. Conclusion: The mainstay of treatment of TS-GCT diffuse type is complete open surgical resection with role of adjuvant radiotherapy/chemotherapy being controversial.